Eliminating Stunting as an Effort to Respect Human Rights (HAM) - Abustan Abustan (Faculty of Law, Universitas Pekalongan, 2022)
Stunting in Indonesia is a picture of poverty and backwardness of society itself. The condition of public health is a worrying sight in the villages. The reality of this very extreme social inequality is clearly occurring in this country. In fact, this happened as a result of failure in development in the human resources sector. What is even worse is the lack of protection and respect for human rights as citizens. Our various national development policies are isolated from their role as instruments of equalization (the great equalizer) which can free poor people from the shackles of poverty. This research was conducted using empirical research and a sociological juridical approach. The aim of the research is to determine the social aspects and dimensions of the implementation of Human Rights, namely the extent to which the government pays attention to handling child nutrition and growth, so that stunting does not worsen in areas (villages). Moreover, remote areas are also part of the unity of the Republic of Indonesia and must be able to become advanced and able to compete fairly with other nations. For this reason, don't let Indonesia's future be filled with many generations who have been exposed to stunting.